PENGARUH KUALITAS PRODUK, CITRA MEREK, PROMOSI, PERSEPSI HARGA, DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN LAPTOP LENOVO (Studi pada Konsumen Lenovo di Kota Semarang) (Students' Journal of Economic and Management, 2016)
The aim of this study was to analyze the effect of product quality, brand image, promotion, price perception, and after-sales service to the purchasing decision Lenovo. The population in this study is the Lenovo brand laptop buyers at the Sun Plaza Simpang Lima Computer. The sample in this study as many as 100 people. The sampling technique used was accidental sampling sampling techniques conducted on respondents who coincidentally encountered in the study when the object of observation is ongoing. The analysis tool used is multiple linear regression. Results of the analysis can be concluded that: product quality has positive influence on purchase decisions. Brand image has positive influence on purchase decisions. Promotion of positive influence on purchase decisions. Perception price positive influence on purchasing decisions. After-sales service has positive influence on purchasing decisions. Keywords: product quality, brand image, promotion, price perceptions, after-sales service and purchasing decisions